2015
DOI: 10.1080/17470218.2014.959709
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Transparency in Free Stems: The Effect of Orthography-Semantics Consistency on Word Recognition

Abstract: A largely overlooked side result in most studies of morphological priming is a consistent main effect of semantic transparency across priming conditions. That is, participants are faster at recognizing stems from transparent sets (e.g., farm) in comparison to stems from opaque sets (e.g., fruit), regardless of the preceding primes. This suggests that semantic transparency may be also consistently associated with some property of the stem word.We propose that this property might be traced back to the consistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 48 publications
(63 reference statements)
9
99
0
Order By: Relevance
“…Our approach moves from a recent work by Marelli, Amenta, and Crepaldi (2015), who have proposed a new measure to address the role of orthography in accessing word meaning. Orthography-Semantics Consistency (OSC) is a corpus-based measure that quantifies the relationship between a letter string and the meanings of all the words in a corpus that share that sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach moves from a recent work by Marelli, Amenta, and Crepaldi (2015), who have proposed a new measure to address the role of orthography in accessing word meaning. Orthography-Semantics Consistency (OSC) is a corpus-based measure that quantifies the relationship between a letter string and the meanings of all the words in a corpus that share that sequence.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Marelli, Amenta, and Crepaldi (2015) showed that the consistency between an orthographic string and the meanings to which it is associated in a large corpus is a relevant predictor in lexical decision experiments. Exploiting irregular mappings between orthography and phonology in English, we were able to compute a phonology-to-semantics consistency measure that dissociates from its orthographic counterpart and tested both measures on lexical decision data taken from the British Lexicon Project (Keuleers et al, 2012).…”
mentioning
confidence: 99%
“…As a test case, we considered the construct developed by Marelli, Amenta, and Crepaldi (2015), Orthography-to-Semantics Consistency (OSC). This is a frequency-weighted average of meaning similarity between any given stem (e.g., DIAL) and all words that include that stem in their orthography (e.g., DIALECT, DIALLED, DIALS, DIALLING, DIALOG, DIALYSIS).…”
Section: Methodsmentioning
confidence: 99%
“…where t is a stem, f rx is the frequency of its k orthographic relatives r x , and t and r x are vectorial representations of meaning as extracted from a distributional semantic model (Marelli et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation